ANALISIS USAHA AGROINDUSTRI DAN PEMASARAN KERIPIK SUKUN EGA SNACK DI DESA KUMANTAN KECAMATAN BANGKINANG KABUPATEN KAMPAR PROVINSI RIAU - Putra Maulana; Fahrial (DINAMIKA PERTANIAN, 2024)
Ega Snack breadfruit chips represent one of the agro-industrial enterprises based in Kumantan Village. The owner of this business employs traditional equipment for production and collaborates with local marketing institutions in Bangkinang to distribute the breadfruit chips. The analysis focuses on three main areas: (1) the characteristics of the entrepreneurs and the profile of the Ega Snack breadfruit chips business; (2) the availability of raw materials, supporting resources, production processes, production costs, revenue, efficiency, business performance, and the added value of Ega Snack breadfruit chips; and (3) the marketing strategies for Ega Snack breadfruit chips within Kampar Regency, Riau Province. This research was conducted using a survey method, with respondents including entrepreneurs and workers from the breadfruit chips agro-industry. Data collection consisted of both primary and secondary data. The analysis encompasses the characteristics of entrepreneurs, business profiles, production processes, the utilization of raw and supporting materials, business performance, and marketing strategies. The research findings indicated the following: (1) The owner of the Ega Snack breadfruit chips business in Kumantan Village was 53 years old, has completed 6 years of education, and possesses 7 years of experience in the industry. The entrepreneur supports two dependents and operates a household-scale business with a workforce of two non-family members and holds a business license. (2) Primary raw materials include breadfruit, while supporting materials encompass water, cooking oil, gas, spices, plastic, stickers, and electricity. The production technology remains basic. The gross income from producing 15 kg of product was IDR 1,500,000, with a net income of IDR 595,313 per production cycle. The efficiency of the Ega Snack breadfruit chips enterprise was measured at 1.66, while the added value from transforming breadfruit into chips was calculated at IDR 14,197.48 per kilogram, yielding a value-added ratio of 47.32%. (3) The marketing of Ega Snack breadfruit chips employed two primary channels: the first channel involved direct sales to retailers, and the second channel involved direct sales to consumers.